Threshold effects of sleep duration and cognitive function in older adults with BMI ≥ 25 kg/m2 - Qiu, Kunyu; Liu, Yilei; Hu, Chengwei; Gu, Jie; Huang, Yanyan (Frontiers in Aging Neuroscience, 2025)
BackgroundIt has been demonstrated that older adults’ cognitive capacities can be improved with sleep duration. However, the relationship between overweight, obesity, and cognitive decline remains a subject of debate. The impact of sleep duration on cognitive performance in seniors with a body mass index (BMI) ≥ 25 kg/m2 is largely unknown. This makes it an intriguing subject to explore further.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES) (2011–2014) with 2,243 participants. Weighted multivariate linear regression and smooth curve fitting were employed to investigate linear and non-linear relationships. A two-part linear regression model was used to determine the threshold effects. Additionally, subgroup analysis and interaction tests were conducted.ResultsResults showed that a negative association was found between sleep duration and scores in the fully adjusted model in the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) test, the Animal Fluency test (AFT), and the Digit Symbol Substitution test (DSST). A two-piecewise linear regression model was then applied to explore the threshold effect of sleep duration on cognitive performance. When sleep duration was less than 5 and 6 h per day, sleep duration was positively correlated with CERAD test scores [ß (95% CI): 2.11 (1.17, 3.05), p < 0.0001], AFT scores [β (95% CI): 0.25 (−0.17, 0.67), p = 0.2376], and DSST scores [ß (95% CI): 0.49 (−0.57, 1.56), p = 0.3654]. However, there was a threshold effect where sleep duration reached the three inflection points.ConclusionIn overweight and obese older adults, there is a clear inverted U-shaped relationship between sleep duration and cognitive function, with consistent results across different subgroups. Sleep durations of around 5–6 h may help prevent cognitive decline in older adults with a BMI ≥ 25 kg/m2.